PENYAKIT VIRUS EBOLA - Henny Elfira Yanti; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Ebola virus disease has known as Ebola hemorrhagic fever (EHF) is an acute viral syndrome characterized by fever and bleeding witha high mortality rate in humans and non human (primates). The current outbreak inWestern Africa is the largest ebola outbreak since theebola virus was first discovered in 1976. The first EHF case that reemerged back in Africa occurred in March 2014 and in Desember 29th2014 had been revealed 20,153 cases and 7,883 deaths. The virus is transmitted from wild animals and spread in the human populationthrough human –to -human transmission. Ebola virus infection is characterized by immunosuppression and systemic inflammatoryresponse. Both condition cause the damage of blood vessels, coagulation and disorders of the immune system, leading to multiple organfailure and shock. Until now there are no ebola standards treatment guidelines. However, the life survival increased with early supportivecare such as rehydration and symptomatic treatment.